2022
DOI: 10.1001/jama.2022.12759
|View full text |Cite
|
Sign up to set email alerts
|

Association of Younger vs Older Ages With Changes in Incidence of Stroke and Other Vascular Events, 2002-2018

Abstract: IMPORTANCE Some studies have reported increasing stroke incidence at younger ages (<55 years) but have often relied only on administrative data, and more population-based studies of adjudicated stroke are required. An understanding of the drivers of any increase in incidence of young stroke also requires comparisons with stroke trends at older ages and with trends in incidence of other vascular events at younger ages.OBJECTIVE To determine temporal changes in incidence of stroke and other major vascular events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
8
25
3
Order By: Relevance
“…We were also reassured by the same directional change of incidence of TIA and stroke at younger ages in studies that reported both, and by the observation in our own study, that the incidence of disabling stroke at younger ages is increasing. 18 In relation to other potential biases, the relative increase in magnetic resonance brain imaging use over time in TIA/ stroke referrals has been similar at younger vs older ages in our own study and where it has been reported elsewhere. 4,18,49 Moreover, the similar increase in incidence of TIA and stroke at younger ages does not suggest diagnostic drift from TIA to stroke owing to increased use of magnetic resonance imaging.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…We were also reassured by the same directional change of incidence of TIA and stroke at younger ages in studies that reported both, and by the observation in our own study, that the incidence of disabling stroke at younger ages is increasing. 18 In relation to other potential biases, the relative increase in magnetic resonance brain imaging use over time in TIA/ stroke referrals has been similar at younger vs older ages in our own study and where it has been reported elsewhere. 4,18,49 Moreover, the similar increase in incidence of TIA and stroke at younger ages does not suggest diagnostic drift from TIA to stroke owing to increased use of magnetic resonance imaging.…”
Section: Discussionsupporting
confidence: 80%
“…18 However, although we showed that traditional vascular risk factors were highly prevalent and poorly controlled among young patients with stroke compared with the age-matched underlying population in the present population, 18 they did not appear to explain the increase of stroke incidence, particularly as incidence of myocardial infarction at younger ages is continuing to fall. 18 The impact of other emerging vascular risk factors, such as air pollution, appear to be age-specific, 90 and long working hours are more strongly associated with risk of stroke than myocardial infarction. 91 We showed that the age-specific divergence in stroke incidence was consistent for men and women, suggesting that sex-specific factors, such as pregnancy and oral contraceptive use, are unlikely to be major drivers, although we could not rule out an association of possible increases in exposure to environmental estrogen over time.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…This might be partially attributed to the relatively small sample size of the study. However, the significant increase in incidence of stroke and TIA was still seen in individuals younger than 55 years without these risk factors, as Li et al reported, which supported our findings ( 29 , 30 ). Moreover, in our study, we found that the prevalence of aPLs in lupus patients with ICVD was 25%–34%, and the incidence of aPLs positivity, especially aCL and LA positivity, was significantly higher versus patients in the non-ICVD group.…”
Section: Discussionsupporting
confidence: 93%